2021
DOI: 10.35833/mpce.2020.000208
|View full text |Cite
|
Sign up to set email alerts
|

Electric Vehicle Charging Simulation Framework Considering Traffic, User, and Power Grid

Abstract: The traffic and user have significant impacts on the electric vehicle (EV) charging load but are not considered in the existing research. We propose a novel integrated simulation framework considering the traffic, the user, and power grid as well as the EV traveling, parking and charging based on cellular automaton (CA). The traffic is modeled by the traffic module of the proposed framework based on CA, while the power grid and user are modeled in the EV charging module. The traffic flow, user' s charging pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The SOC distribution must be considered when determining the power demand. Many factors affect the SOC distribution, e.g., the distance traveled by the EVs, the market share of different types of EVs, the charging rate, and the initial SOC after the EV is connected to the power grid [22]. Many studies have shown that a more accurate forecast of the SOC can significantly reduce the number of decision variables, reduce the time for formulating charging strategies, and maximize the energy utilization [23].…”
Section: ) Transition Of Combined Soc Distributionmentioning
confidence: 99%
“…The SOC distribution must be considered when determining the power demand. Many factors affect the SOC distribution, e.g., the distance traveled by the EVs, the market share of different types of EVs, the charging rate, and the initial SOC after the EV is connected to the power grid [22]. Many studies have shown that a more accurate forecast of the SOC can significantly reduce the number of decision variables, reduce the time for formulating charging strategies, and maximize the energy utilization [23].…”
Section: ) Transition Of Combined Soc Distributionmentioning
confidence: 99%
“…Because for each set of EV load profile(generated from individual one-way travel pattern) samples are i.i.d. [50] which naturally works on Gibbs sampler and load profile probability distribution are not time sensitive since the overall traffic conditions will not change rapidly in certain districts. Thus, a high-dimension probability distribution for EV load profile including TOA, TOD and ETC is demonstrated in this study.…”
Section: ) Gibbs Samplermentioning
confidence: 99%
“…The impact of 6 Teslas (Model S and X) which joined only in the last third of the trial is clearly evident from the increases in both the peak power and the peak-to-average power ratio. [53,[58][59][60][61]. The simulation results are readily tested against real data to refine the models and reveal useful insights.…”
Section: Fast Charging Demandmentioning
confidence: 99%
“…To simplify further analysis and guide design, the results can be represented stochastically, i.e., in terms of a characteristic probability distribution function, mean, and variance [31,50,53,55,65,[70][71][72][73][74][75]. (iii) Agent-based computer simulations of EV travel and charging patterns attempt to predict the value of key parameters, such as charging time, location, and the associated impacts on the electricity grid, and to test the sensitivity of those parameters to factors such as the mix of EVs and charging options, the topology and scale of the road and electricity networks, driver behaviours, the cost to charge, and various other factors of interest [53,[58][59][60][61]. The simulation results are readily tested against real data to refine the models and reveal useful insights.…”
Section: Fast Charging Demandmentioning
confidence: 99%